Rewired NFκB signaling as a potentially actionable feature of activated B‐cell‐like diffuse large B‐cell lymphoma. (8th September 2016) - Knittel, Gero; Liedgens, Paul; Korovkina, Darya; Pallasch, Christian P.; Reinhardt, Hans Christian
Abstract: Diffuse large B‐cell lymphoma (DLBCL) is the most common type of aggressive lymphoma in the Western world and remains a clinical challenge. Two types of DLBCL are distinguishable, namely a germinal center B‐cell‐like phenotype (GCB) and an activated B‐cell‐like phenotype (ABC). Particularly ABC‐DLBCL is difficult to treat, as this subentity typically displays resistance against frontline chemo‐immune therapy. Through the availability of novel experimental technologies, such as next‐generation sequencing and cutting‐edge mouse models, we recently caught an unprecedentedly detailed glimpse at the genomic and biological features of ABC‐DLBCL. Currently, a picture is emerging which suggests that ABC‐DLBCL critically depends on sustained activity of the NFκB pathway, which, among others, is achieved through numerous distinct genetic aberrations, including CD79A/B ‐, CARD11 ‐, and MYD88 mutations. Further genomic aberrations include amplifications of BCL2 and inactivating mutations in PRMD1 . These molecular insights have spurred the development of novel autochthonous mouse models that faithfully mimic the biology and genetics of human ABC‐DLBCL and could serve as preclinical platforms in future experiments. Furthermore, our genomic understanding of the disease now enables us to develop and validate novel targeted therapeutic intervention strategies that aim at decapitating non‐physiological NFκB activity and repressing anti‐apoptotic BCL2 signaling. In this review, we highlight these recent developments and make suggestions for further tool development and the design and stratification of future clinical trials.